Characterization of the leaf microbiome from whole-genome sequencing data of the 3000 rice genomes project - Roman-Reyna, Veronica; Pinili, Dale; Borja, Frances Nikki; Quibod, Ian Lorenzo; Groen, Simon C.; Alexandrov, Nikolai; Mauleon, Ramil; Oliva, Ricardo (Research Square Platform LLC, 2020)
The crop microbial communities are shaped by interactions between the host, microbes and the environment, however, their relative contribution is beginning to be understood. Here, we explore these interactions in the leaf bacterial community across 3,024 rice accessions.Findings: By using unmapped DNA sequencing reads as microbial reads, we characterized the structure of the rice bacterial microbiome. We identified central bacteria taxa that emerge as microbial “hubs” and may have an influence on the network of host-microbe interactions. We found regions in the rice genome that might control the assembly of these microbial hubs. To our knowledge this is one of the first studies that uses raw data from plant genome sequencing projects to characterize the leaf bacterial communities. Conclusion: We showed, that the structure of the rice leaf microbiome is modulated by multiple interactions among host, microbes, and environment. Our data provide insight into the factors influencing microbial assemblage in the rice leaf and also opens the door for future initiatives to modulate rice consortia for crop improvement efforts.